BRUP‐1, an intracellular bilirubin modulator, exerts neuroprotective activity in a cellular Parkinson's disease model. Issue 1 (20th March 2020) - Kataura, Tetsushi; Saiki, Shinji; Ishikawa, Kei‐ichi; Akamatsu, Wado; Sasazawa, Yukiko; Hattori, Nobutaka; Imoto, Masaya
Abstract: Bilirubin, the end product of heme redox metabolism, has cytoprotective properties and is an essential metabolite associated with cardiovascular disease, inflammatory bowel disease, type 2 diabetes, and neurodegenerative diseases including Parkinson's disease (PD). PD is characterized by progressive degeneration of nigral dopaminergic neurons and is associated with elevated oxidative stress due to mitochondrial dysfunction. In this study, using a ratiometric bilirubin probe, we revealed that the mitochondrial inhibitor, rotenone, which is widely used to create a PD model, significantly decreased intracellular bilirubin levels in HepG2 cells. Chemical screening showed that BRUP‐1 was a top hit that restored cellular bilirubin levels that were lowered by rotenone. We found that BRUP‐1 up‐regulated the expression level of heme oxygenase‐1 (HO‐1), one of the rate‐limiting enzyme of bilirubin production via nuclear factor erythroid 2‐related factor 2 (Nrf2) activation. In addition, we demonstrated that this Nrf2 activation was due to a direct inhibition of the interaction between Nrf2 and Kelch‐like ECH‐associated protein 1 (Keap1) by BRUP‐1. Both HO‐1 up‐regulation and bilirubin restoration by BRUP‐1 treatment were significantly abrogated by Nrf2 silencing. In neuronal PC12D cells, BRUP‐1 also activated the Nrf2‐HO‐1 axis and increased bilirubin production, resulted in the suppression of neurotoxin‐induced cell death, reactive oxygen species production, and protein aggregation, which are hallmarks of PD. Furthermore, BRUP‐1 showed neuroprotective activity against rotenone‐treated neurons derived from induced pluripotent stem cells. These findings provide a new member of Keap1‐Nrf2 direct inhibitors and suggest that chemical modulation of heme metabolism using BRUP‐1 may be beneficial for PD treatment. Abstract : Since bilirubin levels were decreased in patients with Parkinson's disease (PD), we searched for compounds that restore bilirubin levels by using a ratiometric bilirubin probe, Flag‐UnaG‐2A‐mCherry, and identified BRUP‐1. We also found that BRUP‐1 inhibited the binding of Keap1 to Nrf2 leading to the activation of Nrf2‐HO‐1 pathway, thereby increasing bilirubin level. BRUP‐1 showed potent neuroprotective activity through the activation of Nrf2‐HO‐1‐bilirubin pathway in a PD model using neuronal PC12D cells. Neuroprotective activity of BRUP‐1 was also shown in iPSC‐derived neurons, which suggests that chemical modulation of heme metabolism using BRUP‐1 may be beneficial for treatment of PD.